Strand specificity of DNA unwinding by RecBCD enzyme. - Braedt, G (1989)
RecBCD enzyme (exonuclease V) of Escherichia coli unwinds DNA, frequently forming asymmetric structures with two single-stranded tails of unequal length abutting a single-stranded loop at the junction with double-stranded DNA. Their lengths are consistent with the longer tail being one strand of the duplex and the loop plus the shorter tail being the other strand. The strand polarity of the unwinding was determined by labeling the 3' or 5' ends of duplex DNA with biotinylated nucleotides, reacting the DNA with RecBCD enzyme, and distinguishing the labeled ends, in the electron microscope, by their binding to streptavidin-gold complex. The shorter tail was formed from the DNA strand with its 3' terminus at the duplex end where RecBCD enzyme entered. We conclude that RecBCD enzyme unwinds DNA by forming a loop on the strand with a 3' end at the entry point. This result is concordant with a previously proposed model of recombination, which we discuss.